SPORT COMMUNICATION: REVEALING THE USE OF INSTRUCTIONAL COMMUNICATION ON FOOTBALL COACHING PROCESS - Dicky Wahyudi; Yun Fitrahyati Laturrahkmi (Profetik: Jurnal Komunikasi, 2022)
ASIFA is one of the most successful international standard football academies in football coaching. This success is inseparable from the communication process between coaches and students during coaching. During this time, research on sports communication highlighted the interaction between coaches and students that had not been widely studied from an instructional communication perspective. Therefore, this research aimed to identify the process of instructional communication between coaches and students in football coaching at ASIFA. This research used a descriptive qualitative method with three data collection techniques, i.e., observation, a document study, and in-depth interviews with coaches, students, and football coaching experts. The research results indicated that the process of instructional communication between coaches and students in football coaching at ASIFA could be identified through six interrelated elements: 1) Context; 2) Source – Sender; 3) Content – Message; 4) Instructional Strategy; 5) Receiver; and 6) Feedback. Through the perspective of instructional communication, it was found that there were conceptual differences between the roles of coaches and students in the coaching process. Practice-based coaching tended to use a rhetorical approach (one-way communication). Meanwhile, non-practical-based coaching used a relational approach (two-way communication). Then, this research contributed by producing a quadrant model of coaching communication in football coaching.